IMPROVING THE QUALITY OF EDUCATION IN REMOTE AREAS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Improving the quality of education in remote and rural areas is a pressing concern for many developing countries, including Uzbekistan. Children living far from urban centers often face challenges such as lack of qualified teachers, limited resources, and poor infrastructure. Education is a key driver of development, and ensuring that children in rural areas receive the same quality of education as their urban peers is critical to achieving equity. This article explores effective strategies that can be implemented to enhance educational quality in remote regions.